A conserved Vac8/ARMC3-PtdIns3K-CI cascade regulates autophagy initiation and functions in spermiogenesis by promoting ribophagy. Issue 12 (2nd December 2021) - Lei, Yuqing; Zhang, Xueguang; Xu, Qingjia; Liu, Shiyan; Li, Chunxia; Jiang, Hui; Lin, Haocheng; Kong, Eryan; Liu, Jiaming; Qi, Shiqian; Li, Huihui; Xu, Wenming; et al.
ABSTRACT: Macroautophagy/autophagy is special because the double-layer lipid-formed autophagosome is formed by de novo generation. Phosphatidylinositol-3-phosphate (PtdIns3P) produced by class III phosphatidylinositol 3-kinase complex I (PtdIns3K-CI) is an essential source lipid for the formation of autophagosomes. However, how autophagy is initiated is unknown. In other words, the mechanism by which PtdIns3K-CI is recruited to the phagophore assembly site (PAS) to initiate autophagosome formation is unclear. We recently uncovered the pivotal role of yeast Vac8 in autophagy initiation through the recruitment of PtdIns3K-CI to the PAS. N-terminal palmitoylation of Vac8 anchors it to the vacuole membrane, and the middle ARM domains bind PtdIns3K-CI, leading to the generation of PtdIns3P at the PAS and subsequent autophagosome formation. We found that mouse ARMC3 is the homolog of yeast Vac8 and that its autophagic roles are conserved. Interestingly, spermatids from mice with Armc3 deletion showed blocked ribophagy, low energy levels of mitochondria and motionless flagella, which caused male infertility. These findings revealed a germ tissue-specific autophagic function of ARMC3 in complex eukaryotic species.